ANALISIS PENGARUH EXPERIENTIAL MARKETING, KUALITAS PELAYANAN DAN LOKASI TERHADAP REPEAT PURCHASE DI HOTEL COMO UMA UBUD, BALI. - Ida Ayu Gede Bulan Julyantari; Anak Agung Putu Agung; I Made Surya Prayoga (EMAS, 2023)
Repeat purchase refers to a condition in which consumers make purchases more than once or repeatedly. Repeat purchase is one of the things that companies must pay attention to. With consumers making a repeat purchase, it will automatically affect the company’s revenue which in turn will help the company to develop and remain in the midst of existing competition. This study aims to determine how the effect of experiential marketing, service quality, and location on repeat purchases at COMO Uma Ubud, Bali. The population of this research is the consumers at COMO Uma Ubud, Bali. The sample in this study amounted to 105 respondents who were determined based on the purposive sampling method. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that experiential marketing, service quality, and location have a positive and significant effect on repeat purchases at COMO Uma Ubud, Bali. This research still needs to develop further related research variables. It is hoped that the next research will be able to develop and test the influence of other variables that affect repeat purchases such as customer satisfaction, price and company image.